A Framework for Bundling Climate-Smart Agriculture (CSA) and Climate Information Services (CIS) in Ethiopia - Tesfaye, Kindie; Tamene, Lulseged D.; Demissie, Teferi Dejene; Ahmed, Jemal Seid; Haile, Aynalem; Mekonnen, Kindu; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Ethiopia is increasingly impacted by climate change and variability because of its greater reliance on climate-sensitive economic sectors such as agriculture. The impacts of climate change and variability are greater on a poor section of the rural community in particular because of their weak adaptive capacities. In recent years, there has been an increasing focus on promoting climate-smart agriculture (CSA) and climate information services (CIS) to improve climate risk management and adaptation of smallholders to climate change in Ethiopia. However, CSA and CIS are rarely provided to farmers in an integrated manner. Therefore, considering the current agricultural technology development and dissemination landscape and the growing digital climate agro-advisory services in the country, a CSA and CIS budling framework is developed for Ethiopia. Bundling of CSA and CIS is expected to empower farmers to make appropriate decisions on a seasonal and intra-seasonal basis, minimize 'technology failure' due to climate variability and enhance adoption of new or existing CSA technologies/practices, reduce yield loss due to climate variability, and farm costs, and increase household income and food security and enhances resilience. Moreover, the bundling framework creates an opportunity for a platform to integrate tools, technologies, and services provided by different institutions and actors. The framework is validated through stakeholder feedback, and it is expected to guide the scaling of bundled services to smallholders.